Developing the risk predictor of chronic suppurative otitis media in association with hypersensitivity state. - Shahrjerdi, Behzad (2012)
Chronic suppurative otitis media (CSOM) is a main cause of acquired hearing impairment especially in developing countries. In view of worldwide burden of CSOM, recognizing the risk factors that contribute to the pathogenesis of CSOM is indispensable. There are some evidences regarding the relationship between hypersensitivity states and middle ear effusion; however the association between allergy and CSOM has not been well documented. To evaluate the association between allergy and chronic suppurative otitis media (CSOM). A comparative cross sectional study was carried out on 2 groups of subjects. 62 patients who were under regular otorhinolaryngology clinic (HUSM) follow up for CSOM were in the case group. The subjects in the control group were selected from USM staffs with no ear pathology. Meticulous history was taken and otoscopic examination and pure tone audiometry (PTA) were conducted. Subsequently, skin prick test was performed for all subjects to establish the presence of allergy. A total of 124 cases which included 62 patients with CSOM and 62 controls participated in this study. The age has been ranging from 15 to 70 years involving 33.1% of males and 66.9% of females. The commonest positive reaction to the allergens was noticed as Blomia Tropicalis and Dermatophagoides in both CSOM and control groups which are considered as house dust mite. The prevalence of allergy in CSOM and control groups was detected as 59.7% and 30.6% respectively. The analysis of the data showed a significant association between allergy and CSOM (p=0.001). The range of conductive hearing loss (CHL) in CSOM cases was from 5 to 50 dB. The Mean (SD) of CHL in allergic and non-allergic CSOM subjects was reported as 28.5(11.2) and 25.4(12.8) respectively. However, no significant relation between severity of hearing loss and presence of allergy in CSOM patients was noted (p=0.327). It seems that the hypersensitivity states have a role in the pathogenesis of CSOM. However, we suggest for the further inclusive studies in different populations to establish this association.